Ubóstwo rodzin w Polsce wyzwaniem dla Kościoła - Przygoda, Wiesław (Studia Pastoralne, 2026)
Economic and social conditions of families are diverse. There are a lot of families of upper and middle class in Poland. According to the report of the Central Statistical Office (GUS) of 2014 entitled: The living conditions of families in Poland there are families in Poland which suffer poverty and are not able to secure even basic needs of their members. It particularly regards children. These families, regardless the causes of their poverty, represent a main challenge for the social services, but also for the Church. Besides material, mental and social needs the Church seeks also to meet spiritual needs of the members of these families. The problem of this study can be summarized in the question: how serious is the problem of poverty among families in Poland and how the Church can support them in the process of overcoming poverty and its consequences? In addition some proposals will be presented regarding ecclesiastical development aid for children from dysfunctional families.